2009
DOI: 10.1029/2008jb005958
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic processes in the Alaska subduction zone by combined 3‐D b value imaging and targeted seismic tomography

Abstract: [1] We combine two complementary seismological methods to study the deep roots of arc volcanism in the Alaskan subduction zone: targeted seismic body wave tomography and imaging of the relative size distribution (b value) of earthquakes. For the tomography we apply a staggered inversion scheme, starting with the minimum 1-D velocity model, progressing to a 3-D velocity model. Inversions are based on traveltime data from about 5500 events with approximately 100,000 P and 50,000 S high-quality arrivals, allowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 63 publications
3
30
0
Order By: Relevance
“…1). In this segment, continental arc volcanism results from subduction of the ∼47 Ma Pacific oceanic plate at the Aleutian trench beneath 30-to 40-km thick continental crust of the North American plate (Fliedner and Klemperer 2000;EberhartPhillips et al 2006;van Stiphout et al 2009). The volcanoes are spaced 50-90 km apart and are located over the 70-to 110-km depth contour of the Wadati-Benioff zone (Kienle and Swanson 1983;Kissling and Lahr 1991;Zhao et al 1995;Eberhart-Phillips et al 2006;van Stiphout et al 2009).…”
Section: Background On Volcanoes: Eruptive and Unrest Activity Since mentioning
confidence: 97%
See 1 more Smart Citation
“…1). In this segment, continental arc volcanism results from subduction of the ∼47 Ma Pacific oceanic plate at the Aleutian trench beneath 30-to 40-km thick continental crust of the North American plate (Fliedner and Klemperer 2000;EberhartPhillips et al 2006;van Stiphout et al 2009). The volcanoes are spaced 50-90 km apart and are located over the 70-to 110-km depth contour of the Wadati-Benioff zone (Kienle and Swanson 1983;Kissling and Lahr 1991;Zhao et al 1995;Eberhart-Phillips et al 2006;van Stiphout et al 2009).…”
Section: Background On Volcanoes: Eruptive and Unrest Activity Since mentioning
confidence: 97%
“…Several important subduction-related parameters are nearly uniform along this arc segment, such as the slab age, dip direction, subduction rate (∼5.5-5.7 cm yr −1 ), and the thickness of the overlying continental crust (DeMets et al 1994;Fliedner and Klemperer 2000;Eberhart-Phillips et al 2006;van Stiphout et al 2009). All of these parameters control significant aspects of arc magma genesis and volcanism (Plank and Langmuir 1988;Syracuse and Abers 2006).…”
Section: Background On Volcanoes: Eruptive and Unrest Activity Since mentioning
confidence: 99%
“…Two trench-parallel lines of volcanic density maxima can also be distinguished for some periods of arc evolution. Spatial and temporal clustering of volcanic activity is also associated with a strongly variable crustal thickness distribution along arcs (e.g., Kodaira et al, 2006Kodaira et al, , 2007 and lateral seismic velocity anomalies changes in the mantle wedges under volcanic arcs (e.g., Zhao et al, 1992Zhao et al, , 2002Zhao, 2001;Tamura et al, 2002;Nakajima and Hasegawa, 2003a,b;van Stiphout et al, 2009). This further points toward a relationship between the mantle wedge processes and crustal growth in intra-oceanic arcs.…”
Section: Small-scale Convection and Thermal-chemical Plumes In The Mamentioning
confidence: 99%
“…Several authors (e.g., Tamura et al, 2002;Honda et al, 2007;Zhu et al, 2009;van Stiphout et al, 2009) analyzed the spatial distribution of volcanism in Japan and Alaska and concluded that several clusters of volcanism can be distinguished in space and time. The typical spatial periodicity of such volcanic clusters is 50-100 km, while their life extent corresponds to 2-7 Myr.…”
Section: Small-scale Convection and Thermal-chemical Plumes In The Mamentioning
confidence: 99%
“…3.2,3.3,3.4,3.5,3.7,3.8,3.9,3.10,3.11,3.12 and 3.13). This seismological feature has been found in all subduction zones which have been studied using seismic tomography (e.g., Zhao et al 1992Zhao et al , 1995Zhao et al , 2000Hasegawa and Zhao 1994;Ma et al 1996;Nakajima et al 2001;McNamara and Pasyanos 2002;Nakamura et al 2003Nakamura et al , 2008Wagner et al 2005Wagner et al , 2010Zhao 2005, 2006a, b;Katsumata et al 2006;Matsubara et al 2008;Wiens et al 2008;van Stiphout et al 2009;Schmandt and Humphreys 2010;Huang et al 2011a;Bianchi et al 2013;Liu et al 2013a, b, and many other references mentioned in this and the following sections). This seismic feature is also consistent with the petrologic results (e.g., Tatsumi 1989;Peacock 1990;Iwamori and Zhao 2000;Hacker et al 2003), indicating that arc magmatism and volcanism are caused by the joint effects of fluids from slab dehydration and corner flow in the mantle wedge.…”
Section: Mantle Wedge and Arc Magmatismmentioning
confidence: 95%